Type 1 Diabetes and Addison's Disease: When the Diagnosis Is Suggested by the Continuous Glucose Monitoring System - Francesco Vinci; Giuseppe d'Annunzio; Flavia Napoli; Marta Bassi; Carolina Montobbio; Giulia Ferrando; Nicola Minuto (MDPI AG, 2021)
Our objective is to emphasize the important role of continuous glucose monitoring (CGM) in suggesting adrenal insufficiency in patients affected by type 1 diabetes. We describe an adolescent girl with type 1 diabetes and subsequent latent Addison's disease diagnosed based on a recurrent hypoglycemic trend detected by CGM. In patients with type 1 diabetes, persistent unexplained hypoglycemic episodes at dawn together with reduced insulin requirement arouse souspicionof adrenal insufficiency. Adrenal insufficiency secondary to autoimmune Addison's disease, even if rarely encountered among young patients, may be initially symptomless and characterized by slow progression up to acute adrenal crisis, which represents a potentially life-threatening condition. Besides glycometabolic assessment and adequate insulin dosage adjustment, type 1 diabetes needs prompt recognition of potentially associated autoimmune conditions. Among these, Addison's disease can be suspected, although latent or paucisymptomatic, through periodic and careful evaluation of CGM data.